UK monetary policy from devaluation to Thatcher, 1967-1982 - Needham, Duncan; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This book charts the course of monetary policy in the UK from 1967 to 1982. It shows how events such as the 1967 devaluation, the collapse of Bretton Woods, the stagflation of the 1970s, and the IMF loan of 1976 all shaped policy. It shows that the'monetarist' experiment of the 1980s was based on a fundamental misreading of 1970s monetary policy.
Keywords: Monetary policy -- Great Britain -- History -- 20th century; Fiscal policy; Great Britain -- Economic policy -- 20th century -- History